Does political knowledge increase support for Europe? A cross country investigation of the attitudes of European citizens - Floriana Cerniglia; Laura Pagani (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study the impact of political knowledge on the attitudes of European citizens towards the possible distribution of responsibilities between European level institutions and national governments in three policy areas: foreign policy, defence and immigration policy. The hypothesis tested is that if citizens are not knowledgeable about how the EU works, they are more likely to be wrong about the consequences of a mismatch in the allocation of competences. In order to identify the causal effect of political knowledge on attitudes we use an instrumental variables approach. The results show that more informed citizens have a considerably higher probability of being in favour of the process of EU integration.
Keywords: H70; D80; 330; European Union; information; attitudes; political economy; Europäische Integration; Meinung; Politisches System; Wissen; EU-Staaten